Association of serum chemokine ligand 21 levels with asthma control in adults (Clinics, 2021)
OBJECTIVES: The chemokine ligand (CCL) 21 regulates the maturation, migration, and function of dendritic cells, and has been implicated in the pathogenesis of asthma. This study aimed to investigate the association between serum CCL21 levels and asthma control. METHODS: The serum levels of CCL21 and other inflammatory cytokines were analyzed in patients with asthma (n=44) and healthy controls (n=35) by enzyme-linked immunosorbent assay. IgE levels and eosinophil counts were determined by turbidimetric inhibition immunoassay and fully automatic blood analysis, respectively. The Asthma Control Test (ACT) questionnaire was used, and spirometry and fractional exhaled nitric oxide (FENO) measurements were performed. A multiple unpaired Student’s t-test was performed to analyze the differences in CCL21 and interleukin levels between patients with asthma and healthy controls. The correlation of CCL21 levels with disease severity was evaluated using the Pearson’s rank correlation test. RESULTS: Serum CCL21 levels were lower in patients with asthma (254.78±95.66 pg/mL) than in healthy controls (382.95±87.77 pg/mL) (po0.001). Patients with asthma had significantly higher levels of IL-1b (19.74±16.77 vs. 2.63±5.22 pg/mL), IL-6 (7.55±8.65 vs. 2.37±2.47 pg/mL), and tumor necrosis factor-a (12.70±12.03 vs. 4.82± 3.97 pg/mL) compared with the controls. CCL21 levels were positively correlated with the ACT score (rs=0.1653, p=0.0062), forced expiratory volume in 1s (FEV1)/forced vital capacity (rs=0.3607, po0.0001), and FEV1 (rs=0.2753, p=0.0003), and negatively correlated with FENO (rs=0.1060, p=0.0310). CCL21 levels were negatively correlated with serum IgE levels (rs=0.1114, p=0.0268) and eosinophil counts (rs=0.3476, po0.0001). CONCLUSIONS: Serum CCL21 levels may be a new biomarker for assessing asthma control.